Business Intelligence Research (2010–2026): A Scopus-Based Bibliometric Assessment of Publication Growth and Conceptual Development - Loso Judijanto; Sopyan Sopyan; Rahmawati Rahmawati; Nikem Kurnia Ningsih; Tiwuk Herawati (Westscience Press, 2026)
This study provides an overview of the evolution of research within the Business Intelligence (BI) domain between 2010 and 2026 by employing the bibliometric method based on the Scopus database. The study was aimed at discovering publication trends, prominent authors and organizations, collaboration structures, and evolution of the scientific concepts within the BI. Data analysis was performed using VOSviewer in order to create maps of co-authors' networks, citation structures, and keyword associations. The study revealed a growing tendency to publish works on the discussed topic, especially in the recent years, which indicates increased interest in data-driven decision-making processes. As far as co-authorship is concerned, cluster structures have been discovered; some authors served as central nodes of the network. Moreover, citations were used as the indicator of relevance of certain papers, and the results showed that interdisciplinary studies focused on artificial intelligence, machine learning, and big data became dominant. Finally, the topic analysis has shown that artificial intelligence has remained the focal point, while other interesting topics like behavioral analytics and generative artificial intelligence received increased attention.